Knowledge, Attitude and Practice Regarding COVID-19 and its Impact on Dentistry: A Cross-sectional Survey among Nepalese Dentists - Khanal, N.; Singh, A.K. (Kathmandu University Medical Journal, 2020)
Background: Coronavirus Disease, 2019 (COVID-19) is a highly infectious respiratory disease with high transmissibility. Dentists are at inherent risk because of aerosol generating procedures exposing dentists to the respiratory and oral secretions of the patients. Objective: To assess the knowledge, awareness, and practice (KAP) of the Dentists to combat the pandemic which could help shape future guidelines and policies to be implemented in dental settings. Method: This cross-sectional descriptive study included series of multiple-choice questions distributed online, assessing dentists’ KAP towards COVID-19, its impact on dentistry and their psychological well-being. Statistical analysis was performed using SPSS (Statistical Package for Social Sciences) version 20 for mac Operating System (OS). Descriptive statistics was performed, and frequencies of responses were reported in proportion. Non-parametric tests of independence and Chi-square test were performed to see the association between the categorical variables. Result: Around 84% of the respondents accurately answered mode of transmission, 68% inquired about the travel history while only 49% measured the body temperature. Also, only 42% were receiving salary. A statistically significant difference concerning impact and practice during the COVID-19 was observed between general practitioner and specialist working at different work places. Conclusion: Majority of Dentists have good knowledge and awareness but there were certain pitfalls in attitude and practice level calling out for more efficient training programs, precise guidelines, and treatment protocols to put into practice. Also, the mental distress and the financial impact subjected upon dentist require to be further explored determining the association between their mental health during and post COVID-19 outbreak.